Twenty thousand streets under the sky a London trilogy - Hamilton, Patrick 1904-1962 (New York Review Books, 2008)
"Patrick Hamilton may be best known now for the plays Rope and Gaslight and for the classic Alfred Hitchcock and George Cukor movies they inspired, but in his heyday he was no less famous for his brooding tales of London life [...] Twenty Thousand Streets Under the Sky is a tale of obsession and betrayal that centers on a seedy pub in a run-down part of London. Bob the waiter skimps and saves and fantasizes about writing a novel, until he falls for the pretty prostitute Jenny and blows it all. Kindly Ella, Bob's co-worker, adores Bob, but is condemned to enjoy nothing more than the attentions of the insufferable Mr. Eccles; Jenny, out on the street, is out of love, hope, and money. We watch with pity and horror as these three vulnerable and yet compellingly ordinary people meet and play out bitter comedies of longing and frustration." -- Book cover.
Keywords: City and town life -- Fiction; London (England) -- Fiction